TOWARDS A PHENOMENOLOGICALL Y GRO UNDED UNDERSTAN DING OF SOCIAL THEORY. I. SOCIOLOGY, PHENOMENOLOGICALLY GRO UNDED METHODOLOGY AND RADICALIZATION OF CRITERIA - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2015)
The first part of the article aims to specify some reflexive aspects of phenomenologically grounded understanding of sociology. The article seeks to elaborate the internal structure of the problem of rationality and to draw attention to the taken for granted, „seen but unnoticed“, character of ordinary social life in terms of methodologically complicated relationship between scientific mind and common sense. This article aims to provide an argument that the specification of three criteria – a) rationality of social world, b) radical reflexivity, c) epoche of the natural attitude – are the main sources of methodological radicalization of phenomenologically grounded social theory.